IMPROVING THE ABILITY OF WRITING PANTUN USING THE MIND MAPPING METHOD IN CLASS VIII STUDENTS OF SMP NEGERI 2 PEGANTENAN FOR ACADEMIC YEAR 2020/2021 - Fredy Yunanto (KOLONI, 2022)
The Mind Mapping method is a creative way for each student to generate ideas, record what is learned, or plan new assignments. Based on this background, the researchers are interested in taking the title " improvement " ability write pantun with use mind mapping method on student class VIII SMP Negeri 2 Pegantenan " . This research is in the form of classroom action research. The research process was carried out in two cycles. Each cycle consists of; planning, action, observation, and reflection. Data was collected by means of observation, giving lift, and tests. Based on The results of the analysis concluded as follows: (1) The activities of class VIII students of SMP Negeri 2 Pegantenan Pamekasan in writing rhymes with the Mind Mapping method experienced an increase in activity, namely the first cycle of 31 activities, and the second cycle of 46 activities consisting of enthusiastically making concept maps in accordance with the researcher's instructions, asking questions with the researcher to perfect the concept map, and doing the task according to the researcher's instructions. (2) Student responses to the use of the Mind Mapping method in order to increase the ability to write rhymes experienced a positive increase, based on the results of the analysis of student responses to the application of the Mind Mapping method in the first cycle and 48% in the second cycle. This percentage is an accumulation of the results of student responses and is described in chapter IV. (3) Test results In increasing the ability to write rhymes with the Mind Mapping method , the average value increase is positive, namely in the first cycle, the score is 69 and the second cycle is 71. Keywords : Pantun , Mind Mapping